THE INFLUENCE OF LANGUAGE ON BRAIN DEVELOPMENT - Erkinjonova Hilola (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation: article offers a detailed exploration of the vital role language plays in shaping brain development, addressing key areas such as early language learning, bilingualism, emotional intelligence, and the challenges posed by language-related disorders. The content is well-organized and effectively highlights the significant influence of linguistic exposure on cognitive, emotional, and social growth.The discussion on bilingualism is particularly noteworthy, showcasing the mental flexibility and lasting advantages associated with learning more than one language. Additionally, the focus on the importance of early interventions for language disorders underscores the necessity of timely support to foster optimal development.Overall, this is an engaging and insightful piece that clearly demonstrates how language impacts brain function and human potential. It serves as a valuable resource for educators, parents, and anyone keen to understand the intricate connection between language and brain development.